Implementation of the Concept of Islamic Educational Psychology of Contemporary Scholars through the Deep Learning Approach - Muhammad Efendi; Saparudin Saparudin; Emawati Emawati; Era Mutiara Pratiwi; Gazi Gazi (IQRO: Journal of Islamic Education, 2025)
This study examines the implementation of the concept of Islamic educational psychology from the perspective of contemporary scholars through the deep learning approach in improving the quality of learning. The study employed a qualitative approach using library research by reviewing various relevant literature sources, including scientific books, journal articles, and previous studies. Data were analyzed descriptively and analytically through the processes of reviewing, comparing, and synthesizing concepts related to Islamic educational psychology and the deep learning approach. The findings indicate that Islamic educational psychology emphasizes the holistic development of students’ potential, encompassing cognitive, affective, and spiritual dimensions. Therefore, education is not only oriented toward the mastery of knowledge but also toward the formation of morals and personality. Furthermore, the deep learning approach has proven effective in encouraging active student engagement, enhancing conceptual understanding, and developing critical, reflective, and creative thinking skills. This approach is aligned with constructivist principles that position students as active subjects in the learning process, making learning more meaningful and contextual. However, the implementation of this integration still faces several challenges, including limited teacher competence and a learning culture that remains oriented toward memorization. Therefore, strategic efforts are required through improving educator capacity, developing adaptive curricula, and strengthening innovative educational policies. In conclusion, the integration of Islamic educational psychology concepts with the deep learning approach has significant potential to create meaningful and high-quality learning and to produce students who are intellectually, spiritually, and emotionally developed.